2011
DOI: 10.1371/journal.pone.0018799
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Laser Scanning Microscopy for Detection of Schistosoma mansoni Eggs in the Gut of Mice

Abstract: BackgroundThe gold standard for diagnosing Schistosoma mansoni infections is the detection of eggs from stool or biopsy specimens. The viability of collected eggs can be tested by the miracidium hatching procedure. Direct detection methods are often limited in patients with light or early infections, whereas serological tests and PCR methods fail to differentiate between an inactive and persistent infection and between schistosomal species. Recently, confocal laser scanning microscopy (CLSM) has been introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…These results indicated that PZQ is lethal to immature and mature eggs as it caused impairment of egg production which may be due to degenerative changes of the reproductive organs of female worms confirmed by many investigators. (Sarvel AK et al 2006, Conceiço MJ et al 2008, Holtfreter MC et al 2011) NTZ resulted in significant reduction in immature eggs, but not more than 18.5% compared to non-treated control. It could rise the percentage of dead eggs to 30.5% and mature eggs to 51% at different intervals of follow up.…”
Section: Discussionmentioning
confidence: 81%
“…These results indicated that PZQ is lethal to immature and mature eggs as it caused impairment of egg production which may be due to degenerative changes of the reproductive organs of female worms confirmed by many investigators. (Sarvel AK et al 2006, Conceiço MJ et al 2008, Holtfreter MC et al 2011) NTZ resulted in significant reduction in immature eggs, but not more than 18.5% compared to non-treated control. It could rise the percentage of dead eggs to 30.5% and mature eggs to 51% at different intervals of follow up.…”
Section: Discussionmentioning
confidence: 81%
“…Microscopic examination of parasite eggs has been the gold standard for the diagnosis of most parasitic diseases, and ancylostomiasis has been no exception . However, a study by Walana et al showed that the positive rate for parasite eggs was only 0.3%; this positive rate is hyperbolically low compared to 47 147 patients with intestinal parasite infection.…”
Section: Discussionmentioning
confidence: 99%
“…In our research results, NLR, PLR, and EOS were significantly correlated in patients group; therefore, the clinical values of the two inflammatory markers (NLR and PLR) were investigated. More importantly, PLR performed with good identification of ancylostomiasis, which was comparable to or even beyond that of EOS.Microscopic examination of parasite eggs has been the gold standard for the diagnosis of most parasitic diseases, and ancylostomiasis has been no exception 22,23. However, a study by Walana et al24 showed that the positive rate for parasite eggs was only 0.3%; this positive rate is hyperbolically low compared to 47 147 patients with intestinal parasite infection.…”
mentioning
confidence: 82%
“…Morphological studies to assess changes in the reproductive system (Shaw and Erasmus, 1988;Neves et al, 2004) of adult worms are ongoing. Interestingly, morphological studies through scanning confocal laser microscopy for determination of egg viability (Holtfreter et al, 2011) and functional criteria such as labeling the eggs with the Hoechst 33258 fluorescent probe (Sarvel et al, 2006) and intestine histopathology (Conceição et al, 2008) can provide important information regarding this issue. Our findings indicate that the wild isolate from N. squamipes is susceptible to praziquantel.…”
Section: Discussionmentioning
confidence: 99%